Oblicz wartość wyrażenia.
a) 3x - 2- 2x + 5 + 4x gdy x =12
b)3a - b +5a +2b - 6 gdy a = 2 i b = 2
c)x + 2y -3y - 3z + 5z - x gdy x = 5, y = 8, z = 6
d)3(x - 4z + y + 4x - z + 2y) gdy x = 1, y = 2, z = 12


Pilne.!
Dam naj.
Zalezy na czasie.

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-25T20:07:08+01:00
A) 3x - 2- 2x + 5 + 4x gdy x =12

3*12-2-2*12+5+4*12=
36-2-24+5+48=96

b)3a - b +5a +2b - 6 gdy a = 2 i b = 2
3*2-2+5*2+2*2-6=
6-2+10+4-6=12

c)x + 2y -3y - 3z + 5z - x gdy x = 5, y = 8, z = 6
5+2*8-3*8-3*6+5*6-5=
5+16-24-18+30-5=4

d)3(x - 4z + y + 4x - z + 2y) gdy x = 1, y = 2, z = 12
3(1-4*12+2+4*1-12+2*2)
3(1-48+2+4-12+4)=
3(-49)=-147
20 3 20